Chronic urticaria in adults: state-of-the-art in the new millennium - Paulo Ricardo Criado; Roberta Facchini Jardim Criado; Celina Wakisaka Maruta; Vitor Manoel Silva dos Reis (Sociedade Brasileira de Dermatologia, 2015)
Chronic urticaria has been explored in several investigative aspects in the new millennium, either as to its pathogenesis, its stand as an autoimmune or auto-reactive disease, the correlation with HLA-linked genetic factors, especially with class II or its interrelation with the coagulation and fibrinolysis systems. New second-generation antihistamines, which act as good symptomatic drugs, emerged and were commercialized over the last decade. Old and new drugs that may interfere with the pathophysiology of the disease, such as cyclosporine and omalizumab have been developed and used as treatments. The purpose of this article is to describe the current state of knowledge on aspects of chronic urticaria such as, pathophysiology, diagnosis and the current therapeutic approach proposed in the literature.